2020
DOI: 10.1016/j.stem.2020.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Niche-Derived Neuregulin-1 Drives Intestinal Stem Cell Proliferation and Regeneration of Damaged Epithelium

Abstract: The proliferation of intestinal stem cells is maintained by EGF, a key component of the medium required to support organoids ex vivo. Here, we identified that NRG1, not EGF, is up-regulated during tissue repair following injury. NRG1 is expressed in mesenchymal stromal cells, macrophages and Paneth cells. Knockout of NRG1 produced a decrease in cell proliferation within crypts and a reduced capacity to regenerate following injury. Treatment with NRG1 robustly stimulated proliferation in crypts and budding of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
80
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(103 citation statements)
references
References 88 publications
7
80
0
Order By: Relevance
“…In both cases, the ultimate outcome of RAL action is an efficient acute proliferative response of intestinal stem cells and tissue regeneration following damage. Therefore, RAL GTPases are effectors of two pivotal signal transduction pathways within the intestinal epithelium Buchon et al, 2010;Jardé et al, 2020;Jiang et al, 2011;Perochon et al, 2018;Sato et al, 2009;Xu et al, 2011).…”
Section: Ral Gtpases As Regulators Of Signal Transductionmentioning
confidence: 99%
“…In both cases, the ultimate outcome of RAL action is an efficient acute proliferative response of intestinal stem cells and tissue regeneration following damage. Therefore, RAL GTPases are effectors of two pivotal signal transduction pathways within the intestinal epithelium Buchon et al, 2010;Jardé et al, 2020;Jiang et al, 2011;Perochon et al, 2018;Sato et al, 2009;Xu et al, 2011).…”
Section: Ral Gtpases As Regulators Of Signal Transductionmentioning
confidence: 99%
“…We further determined that EGF is not expressed in the mesenchyme but is most abundant in the enterocytes of the villus epithelium, several cell diameters away from the proliferative region of the crypt. We identified a population of subepithelial cells (SECs) that lines the entire villus-crypt axis, marked by a F3 HI /PDGFRA HI /DLL1 HI expression profile, and found that these cells express the EGF-family ligand NEUREGU-LIN1 (NRG1), which has been implicated recently as an important regenerative cue in the murine intestine (Jardé et al, 2020). Given that NRG1 is expressed in mesenchymal cells adjacent to proliferative crypts, we tested the effect of EGF and NRG1 on in vitro ISC growth using fetal human duodenal enteroids.…”
Section: Introductionmentioning
confidence: 99%
“…We also observed a substantial upregulation of nrg1 in the regenerating blastema. NRG1 is a critical factor for the development of NC cells and some NCdC, including SC 32 that promote the proliferation of damaged tissue cells in various models and during regeneration 33,34 . In zebrafish and mouse, NRG1 promotes and stimulates cardiomyocyte proliferation during heart regeneration and repair, respectively 35,38 in an ERBB2-dependent manner 39,40 .…”
Section: Discussionmentioning
confidence: 99%
“…To identify the paracrine mechanism underlying foxd3 + NCdC role in the macrophage response during regeneration, we focused our attention on neuregulin 1 (NRG1), a critical factor for the development of NC cells and of some NCdC, including SC 32 , and that promotes the proliferation of damaged tissue cells in various models and during regeneration 33,34,35 . To determine whether NRG1/ERbB was one of signalling pathways that promote blastemal cell proliferation and macrophage pro-regenerative response, we first assessed the expression level of nrg1 and erbb family members in our model.…”
Section: Nrg1 and Erbb Family Members Are Expressed In Blastemal Cellmentioning
confidence: 99%